Crimean-Congo Hemorrhagic Fever Virus Glycoprotein Proteolytic Processing by Subtilase SKI-1 - Vincent, Martin J. (American Society for Microbiology, 2003)
Crimean-Congo hemorrhagic fever (CCHF) virus is a tick-borne member of the genus Nairovirus, family Bunyaviridae. The mature virus glycoproteins, Gn and Gc (previously referred to as G2 and G1), are generated by proteolytic cleavage from precursor proteins. The amino termini of Gn and Gc are immediately preceded by tetrapeptides RRLL and RKPL, respectively, leading to the hypothesis that SKI-1 or related proteases may be involved (A. J. Sanchez, M. J. Vincent, and S. T. Nichol, J. Virol. 76:7263-7275, 2002). In vitro peptide cleavage data show that an RRLL peptide representing the Gn processing site is efficiently cleaved by SKI-1 protease, whereas an RKPL peptide representing the Gc processing site is cleaved at negligible levels. The efficient cleavage of RRLL peptide is consistent with the known recognition sequences of SKI-1, including the sequence determinants involved in the cleavage of the Lassa virus (family Arenaviridae) glycoprotein precursor. These in vitro findings were confirmed by expression of wild-type or mutant CCHF virus glycoproteins in CHO cells engineered to express functional or nonfunctional SKI-1. Gn processing was found to be dependent on functional SKI-1, whereas Gc processing was not. Gn processing occurred in the endoplasmic reticulum-cis Golgi compartments and was dependent on an R at the −4 position within the RRLL recognition motif, consistent with the known cleavage properties of SKI-1. Comparison of SKI-1 cleavage efficiency between peptides representing Lassa virus GP2 and CCHF virus Gn cleavage sites suggests that amino acids flanking the RRLL may modulate the efficiency. The apparent lack of SKI-1 cleavage at the CCHF virus Gc RKPL site indicates that related proteases, other than SKI-1, are likely to be involved in the processing at this site and identical or similar sites utilized in several New World arenaviruses.